A Comparison Between Coronary Artery Bypass Grafting Surgery and Percutaneous Coronary Intervention for the Treatment of Unprotected Left Main Coronary Artery Disease. Issue 1 (25th October 2012) - Qin, Qing; Qian, Juying; Wu, Xuefeng; Fan, Bing; Ge, Lei; Ge, Junbo
Abstract Background: Unprotected left main coronary artery (ULMCA) disease occurs in 3% to 5% of patients with coronary artery disease and is mainly treated by coronary artery bypass grafting (CABG) surgery. Drug‐eluting stents (DESs) have renewed interest for the percutaneous coronary intervention (PCI) treatment of ULMCA stenosis. This study compared the long‐term clinical outcome of PCI with DESs or CABG in real world patients with ULMCA disease. Hypothesis: PCI with DESs may be a better treatment for ULMCA disease compared with CABG. Methods: Consecutive patients who had coronary revascularization because of ULMCA disease in Zhongshan Hospital, from May 2003 to November 2009, were retrospectively enrolled. They were classified in the PCI or the CABG group according to treatments that were given initially. Of 515 patients having follow‐up data, 233 were treated by PCI, whereas 282 were treated by CABG. The patients in the CABG group were of older age, had higher European System for Cardiac Operative Risk Evaluation (EuroSCORE) and Synergy Between PCI With Taxus Drug‐Eluting Stent and Cardiac Surgery (SYNTAX) scores, and had longer hospitalization stays than the PCI group. Results: At the end of follow‐up, there was no difference in major adverse cardiac and cerebrovascular events between the 2 groups. However, the incidence of cardiac death (0.4% vs 4.6%) in the PCI group was less than that in the CABG group, whereas target vessel revascularization (7.3% vs 3.2%) was higher in the PCI group. Conclusions: In ULMCA disease, CABG tends to be chosen in patients with higher risk according to the EuroSCORE and SYNTAX scores. PCI with DESs seemed to have favorable early and long‐term clinical outcomes compared with CABG in our center. Clin. Cardiol. 2012 DOI: 10.1002/clc.22070 Qing Qin, MD, and Juying Qian, MD, contributed equally to this work. The authors have no funding, financial relationships, or conflicts of interest to disclose.